BAP1‐deficient and VE1‐negative atypical Spitz tumor. (12th June 2015) - Requena, Celia; Sanz, Virginia; Nagore, Eduardo; García‐Casado, Zaida; Rubio, Luis; Guillén, Carlos; Kutzner, Heinz
<x xml:space="preserve">Abstract</x> Atypical Spitz tumor with loss of BAP1 or Wiesner nevus is a peculiar variant of intradermal spitzoid melanocytic neoplasm composed of epithelioid melanocytes with a sheet‐like growth pattern, abundant infiltrating lymphocytes and rare or absent mitotic activity. This subset of atypical spitzoid tumors is characterized by the BRAFV600E mutation and loss of BAP1 expression. Recognition of these lesions is important because they can be a marker for a hereditary BAP1‐associated cancer syndrome. We present an unusual case of sporadic Wiesner nevus that had typical histopathologic features and a BAP1 but not a BRAF mutation. The biological significance of Wiesner nevus is controversial, and little is known about prognosis, particularly in atypical cases like this one.